2020
DOI: 10.3390/microorganisms8050684
|View full text |Cite
|
Sign up to set email alerts
|

MG-MLST: Characterizing the Microbiome at the Strain Level in Metagenomic Data

Abstract: The microbiome plays an important role in human physiology. The composition of the human microbiome has been described at the phylum, class, genus, and species levels, however, it is largely unknown at the strain level. The importance of strain-level differences in microbial communities has been increasingly recognized in understanding disease associations. Current methods for identifying strain populations often require deep metagenomic sequencing and a comprehensive set of reference genomes. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Over the last decade, different approaches have been used to understand the genetic diversity and phylogenetic groups of C. acnes mainly based on single locus sequence analyses (16S rRNA, RecA , tly ) ( Scholz et al, 2014 ; McDowell, 2017 ; Yang et al, 2019 ), multilocus sequence typing (MLST) and more recently combined with whole genome sequence analyses ( Lomholt and Kilian, 2010 ; McDowell et al, 2011 , 2012 , 2013 ; Bangayan et al, 2020 ). While some of those typing methods can identify clonal complexes (CC) and sequence types (STs), they cannot differentiate among the sub-clades of type I strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, different approaches have been used to understand the genetic diversity and phylogenetic groups of C. acnes mainly based on single locus sequence analyses (16S rRNA, RecA , tly ) ( Scholz et al, 2014 ; McDowell, 2017 ; Yang et al, 2019 ), multilocus sequence typing (MLST) and more recently combined with whole genome sequence analyses ( Lomholt and Kilian, 2010 ; McDowell et al, 2011 , 2012 , 2013 ; Bangayan et al, 2020 ). While some of those typing methods can identify clonal complexes (CC) and sequence types (STs), they cannot differentiate among the sub-clades of type I strains.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the genetic diversity of Cutibacterium, recent efforts have focused on taxonomy and genotyping to compare strains associated with acne vulgaris. Originally, methods were based on PCR amplification and sequencing of variable sequences such as 16S rRNA, RecA, and tly, as well as multilocus sequence typing (MLST) encompassing seven to nine genes (McDowell et al, 2011(McDowell et al, , 2012(McDowell et al, , 2013Dreno et al, 2018;Bangayan et al, 2020). More recently, the advent of nextgeneration sequencing (NGS) and bioinformatic technologies has enabled the determination of the genomes of numerous isolates.…”
Section: Introductionmentioning
confidence: 99%
“…MA-GenTA bridges the gap between two commonly used approaches—16S rRNA gene sequencing and mWGS—combining some of the strengths of each ( Table 2 ). Other approaches have been described that attempt to balance cost with informativeness, including metagenomic multilocus sequence typing (MLST) ( 56 ), full-length 16S rRNA profiling ( 57 , 58 ), and shallow-coverage mWGS targeting as few as 0.5 million reads/sample ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of healthy microbiomes playing an important role in human physiology has been built more recently in the history of Science, thanks to molecular biology techniques, mainly cloning and sequencing. Strain-level differences in microbiomes has allowed a better understanding of disease associations, not only with cancer, but with a host of diseases, and this have been achieved with a more detailed study in metagenomic sequencing and, therefore, access to complete genomes, as was the case with Propionibacterium acnes, being able to compare healthy skin microbiomes and those linked to acne, at strain level ( Bangayan et al, 2020 ). Studies using analytical chemistry showed the existence of a complex communication system among bacteria, signaled by quorum sensing molecules, a population density-dependent characteristic, and that can allow adaptations to environmental conditions, such those involving bioluminescence, antibiotic biosynthesis, plasmid conjugation and virulence ( Kiymaci et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%